Application of Balinese Cultural Concepts in the Creation of Neo-Traditional Tattoo Art Works - Mahananda, I Putu Gede Rindra; Pemayun, Tjokorda Udiana Nindhia; Putra, I Gede Jaya (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
This thesis contains a description of the creation of works of tattoo art with the theme "Application of Balinese Cultural Concepts in the Creation of Neo-Traditional Works of Tattoo Art" which was inspired when looking at foreign tattoo styles, namely American traditional tattoos, known as American Traditional (Old School Tattoo). where this tattoo has a very strong characteristic or character, so that the traditional American tattoo style is easily recognized. In Bali itself, there are several adherents of the Neo Traditional tattoo style, one of which is Kink Tattoo Bali, where Kink Tattoo Bali has a similar phenomenon where its tattoo work is recognized by tattoo lovers because Kink Tattoo Bali's work has a strong characteristic or character. so that his work can be easily recognized. The aim to be achieved in this MBKM Internship/Work Practicum activity is to find out the situation in the real world of work and gain experience in the world of work as well as various new work experience skills that can broaden your insight into the scope of tattoo work in the world of work and can deepen your knowledge and techniques. in working on professional tattoo projects in the real world of work. MBKM Internship/Practice activities at Studio Kink Tattoo Bali also aim to hone skills in creating original tattoo works by combining Balinese culture with Neo Traditional tattoo styles. In realizing this tattoo design work, the author used interview, observation, documentation and literature methods. From the title above, there are five tattoo design works in MBKM Internship/Practice activities at Kink Tattoo Bali studio.